Real Driving Emissions (RDE) of a Gasoline PHEV - Saeed, Mohammed; Andersson, Ludvig (My University, 2018)
As the gasoline Plug-In Hybrid Electric Vehicle (PHEV) are growing in popularity due to their potential to decrease the levels of exhaust pollutants in the air, the importance of studying the factors affecting the emission levels on these vehicles has increased. This report describes a Real Driving Emissions (RDE) measurement on a Volvo XC90 T8 which is a gasoline PHEV. The goal of the study is to capture the effects of driver behavior, the driving mode and route choice on the emission levels of the RDE cycles. The measurements are conducted using an MSS (Micro Soot Sensor) which means that emissions considered in this study are limited to soot and CO2. The CO2 is calculated, in the section of Post Test Calculations, using the sampled engine parameters. The dynamic RDE requirements are checked in Real-Time using the AVL InVehicle application. Using this app, it is possible to reach the maximum level of aggressiveness and softness while driving without exceeding the limits. Additionally, this report includes an analysis of the correlations between the afore mentioned factors and where each of the factors has the most impact in an RDE cycle. The Results show that the more aggressive one drive, the more soot will be emitted and the more inclination a road has, the more of CO2 will be emitted. When driving in lower speeds and low state of charge, the pure mode which is one of multiple driving modes is more beneficial when it comes to emissions, while the hybrid mode is a better choice when going at higher speeds, e.g. on the motorway. Note that the tests conducted in this report are not included in this vehicle certification procedures. The vehicle is certified for the required emissions according to EU regulation no 692/2008 and 715/2007 which do not require neither a WLTC test nor an RDE test.
Keywords: Transport; Hållbar utveckling; Maskinteknik; Farkostteknik; Transport; Sustainable Development; Mechanical Engineering; Vehicle Engineering